A Study of Primary Students’ Technology Acceptance and Flow State When Using a Technology-Enhanced Board Game in Mathematics Education - Lin, Yen-Ting; Wang, Tz-Chi (Education sciences, 2022)
Mathematics is a major subject for primary students. However, in mathematics education, many abstract concepts may lead students to lose learning motivation and further affect their learning performance. Therefore, several papers have proposed various board games to support traditional mathematics education. However, teachers have applied traditional board games to support mathematics education in a way that makes it difficult to monitor or capture each student’s learning status and problems during game processes. As mentioned above, this study proposed an educational mathematics board game with mobile and sensor technologies to assist students in learning the concept of prime factorization. The proposed board game can guide students to conduct the game and support teachers to capture the students’ learning status during the game process. To evaluate students’ acceptance and flow state regarding the proposed board game, thirty-nine primary students were invited to participate in an experiment. The experimental results indicated that the students had a high technology acceptance with regard to the proposed board game and high flow state when playing the proposed board game. For high-achieving students, the proposed board game was more entertaining, while low-achieving students might feel a little challenged. In addition, boys were more engaged than girls when playing this board game.